Preoperative Considerations for Teenagers Undergoing Orthopaedic Surgery: VTE Prevention, Mental Health Assessment, Vaping, and Drug Addiction. (July 2021) - Shore, Benjamin J.; Flaugh, Rachel; Shannon, Brett A.; Curran, Patrick; Hogue, Grant
Abstract : Introduction: Adolescents undergoing pediatric orthopaedic surgery typically experience an uncomplicated postoperative course. However, adolescence represents a unique transition period from pediatric to adult physiology. As a result, the astute pediatric orthopaedic surgeon will be aware of unique medical and social scenarios which are relevant to adolescents during the perioperative course including the risk of venous thromboembolism (VTE), prevalence of mental health conditions, and rising use of electronic cigarettes or "vaping" to consume nicotine and cannibas. Discussion: Adolescents are at a greater risk of VTE after pediatric orthopaedic surgery. In particular, adolescent females with a family history of blood clotting disorders and those with a change in mobility after surgery should be considered for prophylaxis. The prevalence of adolescent mental health conditions including anxiety, depression, and behavioral issues is increasing in the United States. Higher levels of preoperative anxiety and the presence of mental health pathology are associated with slower recovery, higher levels of postoperative pain, and the increased likelihood for chronic pain. Several quick screening instruments are available to assess adolescents for preoperative anxiety risk, including the Visual Analogue Scale for Anxiety or the Amsterdam Perioperative Anxiety Information Scale. Unfortunately, electronic cigarettes have become increasingly popular for the consumption of nicotine and cannabis among adolescents. Preoperative use of combustive cigarettes (nicotine/cannabis) represents perioperative risks for induction/anesthesia, postoperative pain, and analgesia requirements and issues with delayed wound and fracture healing. Conclusions: VTE, underlying mental health conditions, and usage of nicotine and cannabis are clear detriments to the recovery and healing of adolescent patients following orthopaedic surgery. Therefore, standardized screening for adolescents before orthopaedic surgery is indicated to identify perioperative risk factors which have negative impacts on functional outcomes.